Comparative response of blood cortisol levels to two different doses of intravenous acth (tetracosactrin) in overweight cats - Lobetti, R.G. (Remo Giuseppe) (University of Pretoria, 2013)
Dissertation (MMedVet (Med))--University of Pretoria, 2001.